Benefits, Limitations, and Measures Concerning the Development of Cooperation between Higher Education Institutions and External Entities - Tetřevová, Liběna; Vlčková, Vladimíra (My University, 2018)
Cooperation between higher education institutions and external entities is a prerequisite for the success of all economic entities and society as a whole in any knowledge-based economy. The aim of the study was to identify, analyze, and evaluate the benefits of, and factors limiting cooperation between higher education institutions and external entities, and identify measures that would contribute to the development of this cooperation from the perspective of managers of public, state, and private higher education institutions carrying out activities in the Czech Republic.
Přínosy, omezení a opatření vedoucí k rozvoji spolupráce vysokých škol s externími subjekty
Keywords: cooperation; higher education institutions; faculties; third mission; Czech Republic; spolupráce; vysoké školy; fakulty; třetí poslání; Česká republika